Polarizing film, circular polarizing plate and display device
By using a protective layer of a high content of monofunctional polymerizable compound in the polarizing film, the problem of degradation of polarization performance caused by pigment diffusion is solved, and the long-term stability of polarization performance and the thickness uniformity of the thin film are achieved.
Patent Information
- Application Number
- CN202210730296.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2017-02-08
- Filing Date
- 2018-02-05
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2038-02-05
AI Technical Summary
During use of the existing polarizing film, pigments are prone to diffuse into the polymer film or adhesive, resulting in a degradation of polarization performance.
Using a protective layer containing more than 60% of the monofunctional polymerizable compound, the pigment diffusion is suppressed through the laminated structure of the cured film, and the polarization performance is maintained.
The degradation of the polarization performance over time is effectively suppressed, and a polarization film which is preferably thin is provided, and the image display quality of the display device is improved.
Smart Images

Figure CN114966942B_ABST
Abstract
Description
[0001] This application is a divisional application of the invention application with application date of February 5, 2018, application number 201810114177.2, and invention name “Polarizing film, circular polarizing plate and display device”. Technical Field
[0002] The present invention relates to a polarizing film, and more particularly to a polarizing film in which a protective layer and a polarizer containing a compound exhibiting dichroism are laminated, and a circularly polarizing plate and a display device having the polarizing film. Background Art
[0003] Conventionally, polarizing films are used by being bonded to image display elements such as liquid crystal cells and EL display elements in various image display panels such as liquid crystal display panels and electroluminescent (EL) display panels.
[0004] As such a polarizing film, a polarizing film having the following structure is known: a protective layer such as a triacetyl cellulose film is laminated on one or both sides of a polarizing film formed by adsorbing and aligning a compound showing dichroism such as iodine and a dichroic dye in a polyvinyl alcohol-based resin film via an adhesive layer. In addition, with the continuous demand for thinner displays in recent years, the polarizing film, which is one of the components of the display, is also required to be further thinned. In response to such a demand, for example, thin host-guest type polarizing films formed of a polymerizable liquid crystal compound and a compound showing dichroism such as Patent Documents 1 and 2 have been proposed.
[0005] Prior art literature
[0006] Patent Literature
[0007] Patent Document 1: Japanese Patent Application No. 2007-510946
[0008] Patent Document 2: Japanese Patent Application Publication No. 2013-37353 Summary of the invention
[0009] Problems to be solved by the invention
[0010] By using the polarizing film described in Patent Documents 1 and 2, it is expected that the film can be further thinned compared to the iodine polyvinyl alcohol type polarizing film. However, when the guest-host polarizer described in Patent Document 1 is attached to a polymer film (protective layer) or a display device, the following problems may occur depending on the external environmental conditions of the polarizer: the pigment diffuses from the polarizer into the polymer film and the adhesive, loses anisotropy, and the polarization performance decreases over time.
[0011] In order to solve the above-mentioned problems, the polarizing film described in Patent Document 2 is configured in an In-Cell manner relative to a front panel (glass substrate) by forming an orientation layer, a polarizing layer and a protective layer on a transparent substrate. However, since the protective layer requires a solvent drying process, depending on the type of solvent contained in the composition for making the protective layer or the type of protective layer constructed, there is a situation in which the compound showing dichroism diffuses into the protective layer during the drying process, and the polarization performance decreases over time.
[0012] Therefore, the object of the present invention is to solve the above-mentioned unique problems that may occur in polarizing films, and to provide a preferably thin polarizing film that can suppress the deterioration of polarizing performance over time. In addition, the object of the present invention is also to provide a circularly polarizing plate and a display device including the polarizing film.
[0013] Means for solving problems
[0014] The present invention provides the following preferred embodiments.
[0015] [1] A polarizing film comprising a protective layer and a polarizer containing a compound exhibiting dichroism, wherein the protective layer is a cured film of a composition containing a polymerizable compound, and the content of the monofunctional polymerizable compound in the composition is 60% by mass or more relative to all the polymerizable compounds contained in the composition.
[0016] [2] The polarizing film according to [1] above, wherein the viscosity of the composition at 27° C. is 120 cps or less.
[0017] [3] The polarizing film according to [1] or [2], wherein the monofunctional polymerizable compound includes a compound having a (meth)acryloyl group.
[0018] [4] The polarizing film according to any one of [1] to [3], wherein the monofunctional polymerizable compound includes a compound having a (meth)acryloyl group and a hydroxyl group.
[0019] [5] The polarizing film according to [4], wherein the compound having a (meth)acryloyl group and a hydroxyl group is represented by the following formula (1).
[0020] [Chemical formula 1]
[0021]
[0022] [In the formula, n represents an integer of 1 to 12,
[0023] A 1 represents O or NH,
[0024] X 1represents a methylene group which may have a substituent, and when n is an integer greater than 2, at least one of the methylene groups may be replaced by an oxygen atom, and the substituents may be the same or different]
[0025] [6] The polarizing film according to any one of [1] to [5] above, wherein the polarizer further contains a polymer of a non-coloring polymerizable liquid crystal compound.
[0026] [7] The polarizing film according to [6] above, wherein the polarizer contains a polymer of a non-coloring polymerizable liquid crystal compound in an amount of 80% by mass or more relative to the total mass of the polarizer,
[0027] The polymer of the non-coloring polymerizable liquid crystal compound exhibits a smectic liquid crystal phase.
[0028] The compound exhibiting dichroism is contained in the form of a polymer aligned with the non-coloring polymerizable liquid crystal compound.
[0029] [8] The polarizing film according to any one of [1] to [7] above, wherein the compound exhibiting dichroism is an azo dye.
[0030] [9] A circularly polarizing plate comprising the polarizing film according to any one of [1] to [8] and a retardation film.
[0031]
[10] The circularly polarizing plate according to [9] above, wherein the retardation film satisfies the following formula (X):
[0032] Re(450nm) / Re(550nm)<1 (X)
[0033] [Where Re(λ) represents the front phase difference value with respect to light of wavelength λnm]
[0034]
[11] A display device comprising the polarizing film described in any one of [1] to [8] above, or the circularly polarizing plate described in [9] or
[10] above.
[0035] Effects of the Invention
[0036] According to the present invention, a preferably thin polarizing film capable of suppressing the temporal degradation of polarization performance can be provided, and a circularly polarizing plate and a display device including the polarizing film can also be provided. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] [ Figure 1 ] represents the structure of one embodiment of the polarizing film of the present invention.
[0038] Description of Reference Numerals
[0039] 1: Polarizer
[0040] 2: Protective layer
[0041] 3: Protective layer
[0042] 10: Polarizing film DETAILED DESCRIPTION
[0043] The polarizing film which is one embodiment of the present invention is a polarizing film in which a protective layer and a polarizer containing a compound exhibiting dichroism are laminated.
[0044] Hereinafter, embodiments of the present invention will be described in detail. It should be noted that the scope of the present invention is not limited to the embodiments described here, and various modifications can be made within the scope that does not impair the gist of the present invention.
[0045] In the present invention, based on Figure 1 The structure of one embodiment of the polarizing film will be described.
[0046] The polarizing film (10) has a structure in which a protective layer (2) is laminated on one surface of the polarizer (1). Another protective layer (3) may also be laminated on the other surface of the polarizer (1). In addition, an oriented film (not shown) may be laminated between the polarizer (1) and the protective layer (2) and / or between the polarizer (1) and the protective layer (3). As required, the polarizing film may have an adhesive layer (not shown) on the side opposite to the side of the protective layer adjacent to the polarizing film. From the perspective of improving the heat resistance of the polarizing film, it is preferred that the adhesive layer is not provided. The adhesive layer has the function of bonding the polarizing film to other components such as the front panel.
[0047] Hereinafter, each component of the polarizing film according to one embodiment of the present invention will be described in detail.
[0048] <Polarizing film>
[0049] The polarizer in the present invention is a film containing a compound exhibiting dichroism, and is preferably a film further containing a polymer of a non-coloring polymerizable liquid crystal compound from the viewpoint of facilitating the control of orientation. When the polarizer further contains a polymer of a non-coloring polymerizable liquid crystal compound, from the viewpoint of orientation, the polarizer is a film formed by orienting the compound exhibiting dichroism in a film composed of a polymer of the non-coloring polymerizable liquid crystal compound, and is preferably a film formed by curing the non-coloring polymerizable liquid crystal compound in a state of being oriented in a horizontal direction relative to the inner surface of the protective layer.
[0050] From the perspective of the orientation of the non-coloring polymerizable liquid crystal compound, the thickness of the polarizer is preferably 0.5 μm to 5 μm, and more preferably 1 μm to 3.5 μm. When the thickness of the polarizer is above the above lower limit, it is not easy to orient in the vertical orientation direction, so there is a tendency for the orientation order to be improved. When the thickness of the polarizer is below the above upper limit, it is not easy to orient in the random orientation direction, so there is a tendency for the orientation order to be improved. The thickness of the polarizer can be measured, for example, using an interference film thickness meter, a laser microscope or a stylus film thickness meter.
[0051] There is no particular limitation on the method for manufacturing the polarizer. For example, the polarizer can be obtained by a method comprising the following steps: a step of applying a composition comprising a non-coloring polymerizable liquid crystal compound and a compound showing dichroism (hereinafter, also referred to as a "polarizer forming composition") to the surface of a substrate, an oriented film or a protective layer to form a coating film; and a step of polymerizing the non-coloring polymerizable liquid crystal compound. Here, it is preferred to polymerize the non-coloring polymerizable liquid crystal compound in an oriented state, especially in a state oriented in a horizontal direction relative to the inner surface of the protective layer. In addition, when the polarizer forming composition contains a solvent, the step of drying the coating film may be included as needed. As drying methods, natural drying, ventilation drying, heating drying, and reduced pressure drying methods can be cited.
[0052] [Non-coloring polymerizable liquid crystal compound]
[0053] The so-called non-coloring polymerizable liquid crystal compound refers to a compound that is colorless, has a polymerizable group and has liquid crystal properties. The polymerizable group refers to a group that participates in the polymerization reaction, preferably a photopolymerizable group. Here, the so-called photopolymerizable group refers to a group that can participate in the polymerization reaction under the action of active free radicals, acids, etc. generated by the photopolymerization initiator described later. As the polymerizable group, vinyl, vinyloxy, 1-chlorovinyl, isopropenyl, 4-vinylphenyl, acryloyloxy, methacryloyloxy, oxypropyl, oxetane, etc. can be cited. Among them, acryloyloxy, methacryloyloxy, vinyloxy, oxypropyl and oxetane are preferred, and acryloyloxy is more preferred. The liquid crystal can be a thermotropic liquid crystal (thermotropic liquid crystal) or a lyotropic liquid crystal (lyotropic liquid crystal).
[0054] The non-coloring polymerizable liquid crystal compound may be a thermotropic liquid crystal compound presenting a nematic liquid crystal phase, or may be a thermotropic liquid crystal compound presenting a smectic liquid crystal phase. In the present invention, from the viewpoint of excellent orientation and higher polarization characteristics, the non-coloring polymerizable liquid crystal compound is preferably a thermotropic liquid crystal compound presenting a smectic liquid crystal phase, and more preferably a thermotropic liquid crystal compound presenting a high-order smectic liquid crystal phase. Among them, more preferably a thermotropic liquid crystal compound presenting a smectic B phase, a smectic D phase, a smectic E phase, a smectic F phase, a smectic G phase, a smectic H phase, a smectic I phase, a smectic J phase, a smectic K phase or a smectic L phase, and further preferably a thermotropic liquid crystal compound presenting a smectic B phase, a smectic F phase, a smectic H phase or a smectic I phase. If the liquid crystal phase formed by the non-coloring polymerizable liquid crystal compound is these high-order smectic liquid crystal phases, a polarizer with higher polarization performance can be manufactured. In addition, as mentioned above, a polarizer with high polarization performance preferably obtains a Bragg peak in X-ray diffraction measurement. Such a polarizer is a polarizer that can obtain a Bragg peak from a high-order structure such as a hexagonal phase or a crystal phase. The Bragg peak is a peak from a periodic structure of molecular orientation, and its periodic interval can be obtained from 3 to Furthermore, from the viewpoint of obtaining higher polarization characteristics, in the polarizer involved in one embodiment of the present invention, the polymer of the non-coloring polymerizable liquid crystal compound preferably exhibits a smectic liquid crystal phase, especially a high-order smectic liquid crystal phase.
[0055] Specific examples of such non-coloring polymerizable liquid crystal compounds include compounds represented by the following formula (A) (hereinafter, sometimes referred to as compound (A)). Such non-coloring polymerizable liquid crystal compounds may be used alone or in combination of two or more.
[0056] U 1 -V 1 -W 1 -X 1 -Y 1 -X 2 -Y 2 -X 3 -W 2 -V 2 -U 2 (A)
[0057] [In formula (A),
[0058] X 1 , X 2 and X 3Each of X and X represents independently a 1,4-phenylene group which may have a substituent or a cyclohexane-1,4-diyl group which may have a substituent. 1 , X 2 and X 3 At least one of them is 1,4-phenylene which may have a substituent. -CH2- constituting the cyclohexane-1,4-diyl group may be replaced by -O-, -S- or -NR-. R represents an alkyl group having 1 to 6 carbon atoms or a phenyl group.
[0059] Y 1 and Y 2 independently represent -CH2CH2-, -CH2O-, -COO-, -OCOO-, a single bond, -N=N-, -CR a =CR b -, -C≡C- or -CR a =N-. a and R b Each of them independently represents a hydrogen atom or an alkyl group having 1 to 4 carbon atoms.
[0060] U 1 represents a hydrogen atom or a polymerizable group.
[0061] U 2 It represents a polymerizable group.
[0062] W 1 and W 2 independently of one another represent a single bond, -O-, -S-, -COO- or -OCOO-.
[0063] V 1 and V 2 Each independently represents an alkanediyl group having 1 to 20 carbon atoms which may have a substituent, wherein -CH2- constituting the alkanediyl group may be replaced by -O-, -S- or -NH-.]
[0064] Among the compounds (A), X is preferably 1 , X 2 and X 3 At least one of the groups is 1,4-phenylene which may have a substituent.
[0065] The 1,4-phenylene group which may have a substituent is preferably unsubstituted. The cyclohexane-1,4-diyl group which may have a substituent is preferably a trans-cyclohexane-1,4-diyl group which may have a substituent, and the trans-cyclohexane-1,4-diyl group which may have a substituent is preferably unsubstituted.
[0066] Examples of the substituent that the optionally substituted 1,4-phenylene group or the optionally substituted cyclohexane-1,4-diyl group may have include alkyl groups having 1 to 4 carbon atoms such as methyl, ethyl and butyl groups, cyano groups and halogen atoms.
[0067] Y 1 Preferably -CH2CH2-, -COO- or a single bond, Y 2 Preferred is -CH2CH2- or -CH2O-.
[0068] U 2 U is a polymerizable group. 1 is a hydrogen atom or a polymerizable group, preferably a polymerizable group. 1 and U 2 All of them are polymerizable groups, and more preferably all of them are photopolymerizable groups. A polymerizable liquid crystal compound having a photopolymerizable group is advantageous in that it can be polymerized under relatively low temperature conditions.
[0069] U 1 and U 2 The polymerizable groups represented by may be different from each other, but are preferably the same. Examples of the polymerizable group include vinyl, vinyloxy, 1-chlorovinyl, isopropenyl, 4-vinylphenyl, acryloyloxy, methacryloyloxy, oxirane, and oxetanyl. Among them, acryloyloxy, methacryloyloxy, vinyloxy, oxirane, and oxetanyl are preferred, and acryloyloxy is more preferred.
[0070] As V 1 and V 2 Examples of the alkanediyl group represented by V include methylene, ethylene, propane-1,3-diyl, butane-1,3-diyl, butane-1,4-diyl, pentane-1,5-diyl, hexane-1,6-diyl, heptane-1,7-diyl, octane-1,8-diyl, decane-1,10-diyl, tetradecane-1,14-diyl and eicosane-1,20-diyl. 1 and V 2 An alkanediyl group having 2 to 12 carbon atoms is preferred, and an alkanediyl group having 6 to 12 carbon atoms is more preferred.
[0071] Examples of the substituent that the optionally substituted alkanediyl group having 1 to 20 carbon atoms may have include a cyano group and a halogen atom. The alkanediyl group is preferably unsubstituted, and more preferably an unsubstituted straight-chain alkanediyl group.
[0072] W 1 and W 2 Independently of each other, preferably a single bond or -O-.
[0073] Specific examples of the compound (A) include compounds represented by formula (1-1) to formula (1-23). When the compound (A) has a cyclohexane-1,4-diyl group, the cyclohexane-1,4-diyl group is preferably a trans isomer.
[0074] [Chemical formula 2]
[0075]
[0076] [Chemical formula 3]
[0077]
[0078] [Chemical formula 4]
[0079]
[0080] Among the exemplified compounds (A), it is preferred to select at least one from the group consisting of compounds represented by formula (1-2), formula (1-3), formula (1-4), formula (1-6), formula (1-7), formula (1-8), formula (1-13), formula (1-14) and formula (1-15).
[0081] The compounds (A) listed above can be used in the polarizer alone or in combination. When two or more non-coloring polymerizable liquid crystal compounds are combined, at least one is preferably the compound (A), and two or more are more preferably the compound (A).
[0082] By combining two or more non-coloring polymerizable liquid crystal compounds, it is possible to maintain liquid crystallinity for a period of time even at a temperature below the liquid crystal-crystal phase transition temperature. The mixing ratio when combining two polymerizable liquid crystal compounds is usually 1:99 to 50:50, preferably 5:95 to 40:60, and more preferably 10:90 to 30:70.
[0083] Compound (A) can be produced by a known method described in, for example, Lub et al. Recl. Trav. Chim. Pays-Bas, 115, 321-328 (1996) or Japanese Patent No. 4719156.
[0084] About the content of the non-coloring polymerizable liquid crystal compound in the composition for forming a polarizer, relative to the solid content of the composition for forming a polarizer, preferably 80% by mass or more, more preferably 82% by mass or more, preferably 99.5% by mass or less, more preferably 99% by mass or less, further preferably 94% by mass or less, particularly preferably 90% by mass or less. When the content of the non-coloring polymerizable liquid crystal compound is within the above range, there is a tendency for the orientation to be improved. Here, the so-called solid content refers to the total amount of the component obtained by removing the solvent from the composition for forming a polarizer. Thus, in the obtained polarizer, relative to the gross mass of the polarizer, it is preferably 80% by mass or more, more preferably 82% by mass or more, preferably 99.5% by mass or less, more preferably 99% by mass or less, further preferably 94% by mass or less, and particularly preferably 90% by mass or less of a polymer of a non-coloring polymerizable liquid crystal compound.
[0085] The polarizer-forming composition may contain a solvent, a polymerization initiator, a sensitizer, a polymerization inhibitor, a leveling agent, and a reactive additive as components other than the non-coloring polymerizable liquid crystal compound and the compound exhibiting dichroism.
[0086] [Compounds showing dichroism]
[0087] The compound showing dichroism contained in the polarizer forming composition refers to a compound showing a property (dichroism) that the absorbance in the long axis direction of the molecule is different from the absorbance in the short axis direction. In a preferred embodiment of the present invention, from the viewpoint that the orientation can be easily controlled, the compound showing dichroism is included in the form of a polymer orientation with a non-coloring polymerizable liquid crystal compound. It should be noted that in a more preferred embodiment of the present invention, the polarizer includes a polymer of a non-coloring polymerizable liquid crystal compound above the above range (for example, more than 80% by mass), and if the polymer of the non-coloring polymerizable liquid crystal compound presents a smectic liquid crystal phase, and the compound showing dichroism is included in the form of a polymer orientation with the non-coloring polymerizable liquid crystal compound, then the orientation is further improved, and a high polarization characteristic can be obtained.
[0088] As a compound showing dichroism, it is preferable that the compound has a maximum absorption wavelength (λ) in the range of 300 to 700 nm. max) compounds. As such compounds showing dichroism, for example, acridine pigments, oxazine pigments, cyanine pigments, naphthalene pigments, azo pigments and anthraquinone pigments can be cited, among which azo pigments are preferred. As azo pigments, monoazo pigments, disazo pigments, triazo pigments, tetraazo pigments and stilbene azo pigments can be cited, preferably disazo pigments and triazo pigments. For compounds showing dichroism, they can be used alone, or in combination of two or more, preferably in combination of three or more. In particular, more preferably in combination of three or more azo compounds.
[0089] Examples of the azo dye include compounds represented by formula (B) (hereinafter referred to as “compound (B)” depending on the case).
[0090] A 1 (-N=NA 2 ) p -N=NA 3 (B)
[0091] [In formula (B),
[0092] A 1 and A 3 A represents independently of each other a phenyl group which may have a substituent, a naphthyl group which may have a substituent, or a monovalent heterocyclic group which may have a substituent. 2 represents a 1,4-phenylene group which may have a substituent, a naphthalene-1,4-diyl group which may have a substituent, or a divalent heterocyclic group which may have a substituent. p represents an integer of 1 to 4. When p is an integer of 2 or more, a plurality of A 2 They may be the same or different from each other.]
[0093] Examples of the monovalent heterocyclic group include groups obtained by removing one hydrogen atom from heterocyclic compounds such as quinoline, thiazole, benzothiazole, thienothiazole, imidazole, benzimidazole, oxazole and benzoxazole. Examples of the divalent heterocyclic group include groups obtained by removing two hydrogen atoms from the above heterocyclic compounds.
[0094] As A 1 and A 3 The phenyl, naphthyl and monovalent heterocyclic groups in A 2The substituents that the p-phenylene, naphthalene-1,4-diyl and divalent heterocyclic groups may have include alkyl groups having 1 to 4 carbon atoms; alkoxy groups having 1 to 4 carbon atoms such as methoxy, ethoxy and butoxy; fluoroalkyl groups having 1 to 4 carbon atoms such as trifluoromethyl; cyano; nitro; halogen atoms; substituted or unsubstituted amino groups such as amino, diethylamino and pyrrolidino groups (the so-called substituted amino group refers to an amino group having 1 or 2 alkyl groups having 1 to 6 carbon atoms, or an amino group in which two substituted alkyl groups are bonded to each other to form an alkanediyl group having 2 to 8 carbon atoms. The unsubstituted amino group is -NH2.). It should be noted that specific examples of the alkyl group having 1 to 6 carbon atoms include methyl, ethyl, butyl and hexyl groups.
[0095] Among the compounds (B), preferred are compounds represented by the following formula (2-1) to formula (2-6).
[0096] [Chemical formula 5]
[0097]
[0098] [In formulas (2-1) to (2-6),
[0099] B 1 ~B 20 Each independently represents a hydrogen atom, an alkyl group having 1 to 6 carbon atoms, an alkoxy group having 1 to 4 carbon atoms, a cyano group, a nitro group, a substituted or unsubstituted amino group (the definitions of the substituted amino group and the unsubstituted amino group are as described above), a chlorine atom or a trifluoromethyl group.
[0100] n1 to n4 represent integers of 0 to 3 independently of each other.
[0101] When n1 is 2 or more, multiple B 2 They can be the same or different from each other.
[0102] When n2 is 2 or more, multiple B 6 They can be the same or different from each other.
[0103] When n3 is 2 or more, multiple B 9 They can be the same or different from each other.
[0104] When n4 is 2 or more, multiple B 14 They may be the same or different from each other.]
[0105] As the anthraquinone dye, a compound represented by formula (2-7) is preferred.
[0106] [Chemical formula 6]
[0107]
[0108] [In formula (2-7),
[0109] R 1 ~R 8 Independently represent hydrogen atoms, -R x 、-NH2、-NHR x 、-NR x 2. -SR x or halogen atoms.
[0110] R x represents an alkyl group having 1 to 4 carbon atoms or an aryl group having 6 to 12 carbon atoms.]
[0111] As the oxazine dye, a compound represented by formula (2-8) is preferred.
[0112] [Chemical formula 7]
[0113]
[0114] [In formula (2-8),
[0115] R 9 ~R 15 Independently represent hydrogen atoms, -R x 、-NH2、-NHR x 、-NR x 2. -SR x or halogen atoms.
[0116] R x represents an alkyl group having 1 to 4 carbon atoms or an aryl group having 6 to 12 carbon atoms.]
[0117] As the acridine dye, a compound represented by formula (2-9) is preferred.
[0118] [Chemical formula 8]
[0119]
[0120] [In formula (2-9),
[0121] R 16 ~R 23 Independently represent hydrogen atoms, -R x 、-NH2、-NHR x 、-NR x 2. -SR x or halogen atoms.
[0122] R x represents an alkyl group having 1 to 4 carbon atoms or an aryl group having 6 to 12 carbon atoms.]
[0123] As R in formula (2-7), formula (2-8) and formula (2-9), x Examples of the alkyl group having 1 to 4 carbon atoms include methyl, ethyl, propyl, and butyl. Examples of the aryl group having 6 to 12 carbon atoms include phenyl, tolyl, xylyl, and naphthyl.
[0124] As the cyanine dye, a compound represented by formula (2-10) and a compound represented by formula (2-11) are preferred.
[0125] [Chemical formula 9]
[0126]
[0127] [In formula (2-10),
[0128] D 1 and D 2 Each independently represents a group represented by any one of formula (2-10a) to formula (2-10d).
[0129] [Chemical formula 10]
[0130]
[0131] n5 represents an integer from 1 to 3.]
[0132] [Chemical formula 11]
[0133]
[0134] [In formula (2-11),
[0135] D 3 and D 4 Each independently represents a group represented by any one of formula (2-11a) to formula (2-11h).
[0136] [Chemical formula 12]
[0137]
[0138] n6 represents an integer from 1 to 3.]
[0139] Regarding the content of the compound showing dichroism in the polarizer forming composition, relative to 100 parts by mass of the content of the non-coloring polymerizable liquid crystal compound, it is preferably 0.1 to 30 parts by mass, more preferably 0.1 to 20 parts by mass, and further preferably 0.1 to 12 parts by mass. When the content of the compound showing dichroism is within the above range, the non-coloring polymerizable liquid crystal compound can be polymerized without disturbing the orientation of the non-coloring polymerizable liquid crystal compound. If the content of the compound showing dichroism is too much, the orientation of the non-coloring polymerizable liquid crystal compound may be hindered. Therefore, the content of the compound showing dichroism can also be determined within the range that the non-coloring polymerizable liquid crystal compound can be kept in a liquid crystal state. It should be noted that, with respect to the content of the compound showing dichroism in the obtained polarizer, from the same viewpoint as above, it is preferably 0.1 to 30 parts by mass, more preferably 0.1 to 20 parts by mass, and further preferably 0.1 to 12 parts by mass relative to 100 parts by mass of the polymer of the non-coloring polymerizable liquid crystal compound.
[0140] The compound showing dichroism can be a polymer of a monomer having a polymerizable group and using the pigment listed above as a skeleton. When the compound showing dichroism is a polymer of a monomer having a polymerizable group and using the above-mentioned pigment as a skeleton, the compound showing dichroism can be further suppressed from transferring to the protective layer. However, when the compound showing dichroism is a polymer, there is a tendency for the orientation to decrease, and therefore, there is a tendency for the polarization performance to decrease. Therefore, in a preferred embodiment of the present invention, the compound showing dichroism does not have a polymerizable group, and its molecular weight is, for example, less than 1000. Through the present invention, even if the compound showing dichroism is not polymerized, the transfer of the compound showing dichroism to the protective layer can be suppressed, and therefore, a polarizing film with excellent polarization performance can be obtained.
[0141] [Solvent]
[0142] The polarizer-forming composition may contain a solvent. As the solvent, a solvent that can completely dissolve the non-coloring polymerizable liquid crystal compound is preferred, and a solvent that is inert to the polymerization reaction of the non-coloring polymerizable liquid crystal compound is preferred.
[0143] Examples of the solvent include alcohol solvents such as methanol, ethanol, ethylene glycol, isopropanol, propylene glycol, ethylene glycol methyl ether, ethylene glycol butyl ether, and propylene glycol monomethyl ether; ester solvents such as ethyl acetate, butyl acetate, ethylene glycol methyl ether acetate, γ-butyrolactone or propylene glycol methyl ether acetate, and ethyl lactate; ketone solvents such as acetone, methyl ethyl ketone, cyclopentanone, cyclohexanone, 2-heptanone, methyl isobutyl ketone, and isophorone; aliphatic hydrocarbon solvents such as pentane, hexane, and heptane; aromatic hydrocarbon solvents such as toluene and xylene, and nitrile solvents such as acetonitrile; ether solvents such as tetrahydrofuran and dimethoxyethane; chlorine-containing solvents such as chloroform and chlorobenzene; and the like.
[0144] These solvents may be used alone or in combination of two or more.
[0145] Relative to the total amount of the above-mentioned polarizer forming composition, the content of the solvent is preferably 50-98 mass %. In other words, the content of the solid component in the polarizer forming composition is preferably 2-50 mass %. When the content of the solid component is less than 50 mass %, the viscosity of the polarizer forming composition decreases, and therefore, the thickness of the polarizer becomes roughly uniform, and thus, there is a tendency to become less likely to produce unevenness in the polarizer. In addition, the content of the solid component can be determined considering the thickness of the polarizer to be manufactured.
[0146] [Polymerization initiator]
[0147] The polarizer-forming composition may contain a polymerization initiator. A polymerization initiator is a compound that can initiate a polymerization reaction of a non-coloring polymerizable liquid crystal compound, etc. As the polymerization initiator, a photopolymerization initiator that generates active radicals under the action of light is preferred.
[0148] Examples of the polymerization initiator include benzoin compounds, benzophenone compounds, alkylphenone compounds, acylphosphine oxide compounds, triazine compounds, iodonium salts, and sulfonium salts.
[0149] Examples of the benzoin compound include benzoin, benzoin methyl ether, benzoin ethyl ether, benzoin isopropyl ether and benzoin isobutyl ether.
[0150] Examples of the benzophenone compound include benzophenone, methyl o-benzoylbenzoate, 4-phenylbenzophenone, 4-benzoyl-4′-methyldiphenyl sulfide, 3,3′,4,4′-tetrakis(tert-butylperoxycarbonyl)benzophenone, and 2,4,6-trimethylbenzophenone.
[0151] Examples of the alkylphenone compound include diethoxyacetophenone, 2-methyl-2-morpholino-1-(4-methylthiophenyl)propane-1-one, 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)butane-1-one, 2-hydroxy-2-methyl-1-phenylpropane-1-one, 1,2-diphenyl-2,2-dimethoxyethane-1-one, 2-hydroxy-2-methyl-1-[4-(2-hydroxyethoxy)phenyl]propane-1-one, 1-hydroxycyclohexylphenyl ketone, and oligomers of 2-hydroxy-2-methyl-1-[4-(1-methylvinyl)phenyl]propane-1-one.
[0152] Examples of the acylphosphine oxide compound include 2,4,6-trimethylbenzoyldiphenylphosphine oxide and bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide.
[0153] Examples of the triazine compound include 2,4-bis(trichloromethyl)-6-(4-methoxyphenyl)-1,3,5-triazine, 2,4-bis(trichloromethyl)-6-(4-methoxynaphthyl)-1,3,5-triazine, 2,4-bis(trichloromethyl)-6-(4-methoxyphenyl)-1,3,5-triazine, 2,4-bis(trichloromethyl)-6-(4-methoxyphenyl)-1,3,5-triazine, 2,4-bis(trichloromethyl)-6-[2-(5-methylfuran-2-yl)] [vinyl]-1,3,5-triazine, 2,4-bis(trichloromethyl)-6-[2-(furan-2-yl)vinyl]-1,3,5-triazine, 2,4-bis(trichloromethyl)-6-[2-(4-diethylamino-2-methylphenyl)vinyl]-1,3,5-triazine and 2,4-bis(trichloromethyl)-6-[2-(3,4-dimethoxyphenyl)vinyl]-1,3,5-triazine, etc.
[0154] As the polymerization initiator, a commercially available polymerization initiator can be used. Examples of commercially available polymerization initiators include Irgacure (registered trademark) 907, 184, 651, 819, 250, and 369 (manufactured by Ciba Specialty Chemicals Co., Ltd.); SEIKUOL (registered trademark) BZ, Z, and BEE (manufactured by Seiko Chemical Co., Ltd.); Kayacure (registered trademark) BP100 and UVI-6992 (manufactured by DOW Chemical Company); ADEKA OPTOMER SP-152 and SP-170 (manufactured by ADEKA Corporation); TAZ-A and TAZ-PP (manufactured by Nippon Siber Hegner Co., Ltd.); and TAZ-104 (manufactured by Sanwa Chemical Co., Ltd.); and the like.
[0155] The content of the polymerization initiator in the polarizer-forming composition can be appropriately adjusted according to the type and amount of the non-coloring polymerizable liquid crystal compound, and is generally 0.1 to 30 parts by mass, preferably 0.5 to 10 parts by mass, and more preferably 0.5 to 8 parts by mass, relative to 100 parts by mass of the content of the non-coloring polymerizable liquid crystal compound. If the content of the polymerization initiator is within the above range, polymerization can be performed without disturbing the orientation of the non-coloring polymerizable liquid crystal compound.
[0156] [Sensitizer]
[0157] The polarizer forming composition may contain a sensitizer. As the sensitizer, a photosensitizer is preferred. Examples of the sensitizer include xanthone compounds such as xanthone and thioxanthone (e.g., 2,4-diethylthioxanthone, 2-isopropylthioxanthone, etc.); anthracene compounds such as anthracene and anthracene containing an alkoxy group (e.g., dibutoxyanthracene, etc.); phenothiazine and rubrene, etc.
[0158] When the polarizer forming composition contains a sensitizer, the polymerization reaction of the polymerizable liquid crystal compound contained in the polarizer forming composition can be further promoted. The amount of the sensitizer used is preferably 0.1 to 30 parts by mass, more preferably 0.5 to 10 parts by mass, and even more preferably 0.5 to 8 parts by mass, relative to 100 parts by mass of the non-coloring polymerizable liquid crystal compound.
[0159] [Polymerization inhibitor]
[0160] The polarizer-forming composition may contain a polymerization inhibitor from the viewpoint of stably advancing the polymerization reaction. The polymerization inhibitor can control the degree of progress of the polymerization reaction of the non-coloring polymerizable liquid crystal compound.
[0161] Examples of the polymerization inhibitor include free radical scavengers such as hydroquinone, alkoxy-containing hydroquinone, alkoxy-containing catechol (e.g., butyl catechol), pyrogallol, and 2,2,6,6-tetramethylpiperidin-1-oxyl radical; thiophenols; β-naphthylamines; and β-naphthols.
[0162] When the polarizer forming composition contains a polymerization inhibitor, the content of the polymerization inhibitor is preferably 0.1 to 30 parts by mass, more preferably 0.5 to 10 parts by mass, and further preferably 0.5 to 8 parts by mass relative to 100 parts by mass of the non-coloring polymerizable liquid crystal compound. If the content of the polymerization inhibitor is within the above range, polymerization can be performed without disturbing the orientation of the non-coloring polymerizable liquid crystal compound.
[0163] [Leveling agent]
[0164] The polarizer forming composition may contain a leveling agent. The so-called leveling agent is a substance that has the function of adjusting the fluidity of the polarizer forming composition and making the film obtained by coating the polarizer forming composition flatter. For example, a surfactant can be cited. As a preferred leveling agent, a leveling agent with a polyacrylate compound as the main component, such as "BYK-361N" (manufactured by BYK-Chemie); and Surflon (registered trademark) "S-381" (manufactured by AGC Seimi Chemical Co., Ltd.), "MEGAFACE (メガフェイス) F-556", "MEGAFACE F-554" (manufactured by DIC Corporation) and the like, a leveling agent with a compound containing fluorine atoms as the main component.
[0165] When the polarizer forming composition contains a leveling agent, the content of the leveling agent is preferably 0.1 to 5 parts by mass, more preferably 0.3 to 5 parts by mass, and further preferably 0.4 to 3 parts by mass, relative to 100 parts by mass of the content of the non-coloring polymerizable liquid crystal compound. When the content of the leveling agent is within the above range, there is a tendency that the non-coloring polymerizable liquid crystal compound is easily oriented in the horizontal direction (horizontally oriented), and the obtained polarizer becomes smoother. When the content of the leveling agent relative to the non-coloring polymerizable liquid crystal compound exceeds the above range, there is a tendency to easily produce unevenness in the obtained polarizer. It should be noted that the polarizer forming composition may contain two or more leveling agents.
[0166] [Reactive Additives]
[0167] The polarizer forming composition may include a reactive additive. As a reactive additive, an additive having a carbon-carbon unsaturated bond and an active hydrogen reactive group in its molecule is preferred. It should be noted that the so-called "active hydrogen reactive group" here refers to a group reactive with respect to a group having active hydrogen such as a carboxyl group (-COOH), a hydroxyl group (-OH), and an amino group (-NH2), and its representative examples are glycidyl, oxazoline, carbodiimide, aziridine, imide, isocyanate, isothiocyanate, maleic anhydride, etc. The number of carbon-carbon unsaturated bonds and active hydrogen reactive groups possessed by the reactive additive is usually 1 to 20, respectively, and preferably 1 to 10, respectively.
[0168] It is preferred that at least two active hydrogen reactive groups exist in the reactive additive. In this case, the plurality of active hydrogen reactive groups may be the same or different.
[0169] The carbon-carbon unsaturated bond possessed by the reactive additive may be a carbon-carbon double bond or a carbon-carbon triple bond, or a combination thereof, preferably a carbon-carbon double bond. Wherein, as a reactive additive, it is preferred that the carbon-carbon unsaturated bond is contained in the form of a vinyl group and / or a (meth) acrylic group ((meth) acryl group). In addition, it is preferred that the active hydrogen reactive group is a reactive additive of at least one selected from the group consisting of an epoxy group, a glycidyl group and an isocyanate group, more preferably a reactive additive having an acrylic group (acryl group) and an isocyanate group.
[0170] Specific examples of reactive additives include compounds having a (meth) acrylic group and an epoxy group, such as methacryloyloxyglycidyl ether and acryloxyglycidyl ether; compounds having a (meth) acrylic group and an oxetane group, such as oxetane acrylate and oxetane methacrylate; compounds having a (meth) acrylic group and a lactone group, such as lactone acrylate and lactone methacrylate; compounds having a vinyl group and an oxazoline group, such as vinyl oxazoline and isopropenyl oxazoline; oligomers of compounds having a (meth) acrylic group and an isocyanate group, such as isocyanatomethyl acrylate, isocyanatomethyl methacrylate, 2-isocyanatoethyl acrylate, and 2-isocyanatoethyl methacrylate, etc. In addition, compounds having a vinyl group, 1,2-vinylidene group, and anhydride, such as methacrylic anhydride, acrylic anhydride, maleic anhydride, and vinyl maleic anhydride, etc., can be cited. Among them, preferred are methacryloyloxy glycidyl ether, acryloyloxy glycidyl ether, isocyanate methyl acrylate, isocyanate methyl methacrylate, vinyloxazoline, 2-isocyanate ethyl acrylate, 2-isocyanate ethyl methacrylate and oligomers thereof, and particularly preferred are isocyanate methyl acrylate, 2-isocyanate ethyl acrylate and oligomers thereof.
[0171] Specifically, a compound represented by the following formula (Y) is preferred.
[0172] [Chemical formula 13]
[0173]
[0174] [In formula (Y),
[0175] n represents an integer from 1 to 10, R 1’ represents a divalent aliphatic or alicyclic hydrocarbon group having 2 to 20 carbon atoms, or a divalent aromatic hydrocarbon group having 5 to 20 carbon atoms. 2’ For example, one is -NH- and the other is >NC(=O)-R 3’ Represents a group. 3’It represents a hydroxyl group or a group having a carbon-carbon unsaturated bond.
[0176] R in formula (Y) 3’ At least 1 R 3’ A group having a carbon-carbon unsaturated bond.]
[0177] Among the reactive additives represented by the above formula (Y), compounds represented by the following formula (YY) (hereinafter, sometimes referred to as compound (YY)) are particularly preferred (wherein n has the same meaning as described above).
[0178] [Chemical formula 14]
[0179]
[0180] As compound (YY), a commercially available product may be used as it is, or may be purified as necessary and used. Examples of commercially available products include Laromer (registered trademark) LR-9000 (manufactured by BASF Corporation).
[0181] When the polarizer-forming composition contains a reactive additive, the content of the reactive additive is usually 0.01 to 10 parts by mass, preferably 0.1 to 5 parts by mass, based on 100 parts by mass of the polymerizable liquid crystal compound.
[0182] <Oriented film>
[0183] In the present invention, the alignment film is a film formed of a polymer compound and has an alignment control force for orienting a non-coloring polymerizable liquid crystal compound in a desired direction.
[0184] The orientation film makes it easy to orient the liquid crystal of the non-coloring polymerizable liquid crystal compound. The state of liquid crystal orientation such as horizontal orientation, vertical orientation, hybrid orientation, and tilted orientation varies depending on the properties of the orientation film and the non-coloring polymerizable liquid crystal compound, and the combination thereof can be selected arbitrarily. For example, if the orientation film is a material that exhibits horizontal orientation as an orientation control force, the non-coloring polymerizable liquid crystal compound can form a horizontal orientation or a hybrid orientation, and if it is a material that exhibits vertical orientation as an orientation control force, the non-coloring polymerizable liquid crystal compound can form a vertical orientation or a tilted orientation.
[0185] Expressions such as horizontal and vertical indicate the direction of the long axis of the oriented non-coloring polymerizable liquid crystal compound with respect to the polarizer plane. For example, vertical orientation means that the long axis of the oriented polymerizable liquid crystal compound is in a direction perpendicular to the polarizer plane. Here, vertical means 90°±20° relative to the polarizer plane.
[0186] As for the orientation control force, when the orientation film is formed of an orientation polymer, it can be arbitrarily adjusted by the surface state and friction conditions, and when the orientation film is formed of a photo-orientation polymer, it can be arbitrarily adjusted by polarized light irradiation conditions, etc. In addition, the liquid crystal orientation can also be controlled by selecting the physical properties such as the surface tension and liquid crystal properties of the non-coloring polymerizable liquid crystal compound.
[0187] As the alignment film formed between the substrate or the protective layer and the polarizer, it is preferred that the alignment film is insoluble in the solvent used when the polarizer is formed on the alignment film and has heat resistance to withstand the heating treatment for removing the solvent or orienting the liquid crystal. As the alignment film, an alignment film formed of an oriented polymer, a photo-aligned film, and a groove alignment film can be cited, preferably a photo-aligned film.
[0188] The thickness of the alignment film is usually in the range of 10 nm to 500 nm, preferably in the range of 10 nm to 200 nm, and more preferably in the range of 30 to 100 nm.
[0189] As oriented polymer, polyamide, gelatin, polyimide with amide bond in molecule and polyamic acid, polyvinyl alcohol, alkyl-modified polyvinyl alcohol, polyacrylamide, polyoxazole, polyethyleneimine, polystyrene, polyvinyl pyrrolidone, polyacrylic acid and polyacrylate etc. as its hydrolyzate can be enumerated.Wherein, preferred polyvinyl alcohol.These oriented polymers can be used alone, and two or more can also be used in combination.
[0190] When the oriented film is formed by an oriented polymer, the oriented film can generally be obtained by the following steps: a step of applying a composition comprising an oriented polymer and a solvent (hereinafter also referred to as an "oriented polymer composition") to a substrate or a protective layer and removing the solvent; or a step of applying the oriented polymer composition to a substrate or a protective layer, removing the solvent, and performing a rubbing process (rubbing method).
[0191] Examples of the solvent include water; alcohol solvents such as methanol, ethanol, ethylene glycol, isopropanol, propylene glycol, methyl cellosolve, butyl cellosolve, and propylene glycol monomethyl ether; ester solvents such as ethyl acetate, butyl acetate, ethylene glycol methyl ether acetate, γ-butyrolactone, propylene glycol methyl ether acetate, and ethyl lactate; ketone solvents such as acetone, methyl ethyl ketone, cyclopentanone, cyclohexanone, methyl amyl ketone, and methyl isobutyl ketone; aliphatic hydrocarbon solvents such as pentane, hexane, and heptane; aromatic hydrocarbon solvents such as toluene and xylene, and nitrile solvents such as acetonitrile; ether solvents such as tetrahydrofuran and dimethoxyethane; chlorinated hydrocarbon solvents such as chloroform and chlorobenzene; etc. These solvents may be used alone or in combination of two or more.
[0192] The concentration of the oriented polymer in the oriented polymer composition may be within a range in which the oriented polymer can be completely dissolved in the solvent, and is preferably 0.1 to 20% by mass, more preferably 0.1 to 10% by mass, based on the solid content of the solution.
[0193] As the oriented polymer composition, a commercially available oriented film material may be used as it is. Examples of commercially available oriented film materials include SUNEVER (registered trademark) (manufactured by Nissan Chemical Industries, Ltd.) and OPTMER (registered trademark) (manufactured by JSR Corporation).
[0194] As a method for coating the oriented polymer composition on a substrate or a protective layer, there can be mentioned known methods such as a coating method such as a spin coating method, an extrusion method, a gravure coating method, a die coating method, a rod coating method, and an applicator method, and a printing method such as a flexographic method. When a polarizing film according to an embodiment of the present invention is manufactured by a continuous manufacturing method using a roll-to-roll method, as the coating method, a gravure coating method, a die coating method, or a printing method such as a flexographic method can generally be used.
[0195] By removing the solvent contained in the oriented polymer composition, a dry film of the oriented polymer can be formed. Examples of the method for removing the solvent include natural drying, ventilation drying, heating drying, and reduced pressure drying.
[0196] The rubbing method includes a method in which a rotating rubbing roller wrapped with a rubbing cloth is brought into contact with an oriented polymer film on a substrate or a protective layer (the oriented polymer film is formed by applying an oriented polymer composition to the substrate or the protective layer and annealing the film).
[0197] The photo-alignment film can be obtained by applying a composition comprising a polymer or monomer having a photoreactive group and a solvent (hereinafter, also referred to as a "photo-alignment film-forming composition") to a substrate or a protective layer and irradiating polarized light (preferably polarized UV light). The photo-alignment film is more preferred because the direction of the orientation control force can be arbitrarily controlled by selecting the polarization direction of the irradiated polarized light.
[0198] The so-called photoreactive group refers to a group that generates liquid crystal orientation ability by irradiation with light. Specifically, it refers to a group that can generate a photoreaction that is the origin of the liquid crystal orientation ability (such as the orientation induction of molecules generated by irradiation with light or isomerization reaction, dimerization reaction, photocrosslinking reaction or photodecomposition reaction, etc.). Among the photoreactive groups, from the perspective of excellent orientation, a group that preferably undergoes dimerization reaction or photocrosslinking reaction. As a photoreactive group that can generate such a reaction as above, it is preferably a group having an unsaturated bond, especially a double bond, and more preferably a group having at least one selected from the group consisting of a carbon-carbon double bond (C=C bond), a carbon-nitrogen double bond (C=N bond), a nitrogen-nitrogen double bond (N=N bond) and a carbon-oxygen double bond (C=O bond).
[0199] As photoreactive groups having C=C bonds, for example, vinyl, polyene, stilbene, stilbazole, stilbazolium, chalcone, and cinnamoyl groups can be cited. As photoreactive groups having C=N bonds, groups having structures such as aromatic Schiff bases and aromatic hydrazones can be cited. As photoreactive groups having N=N bonds, azophenyl, azonaphthyl, aromatic heterocyclic azo, disazo, and formazan groups can be cited, as well as groups with oxyazobenzene as the basic structure. As photoreactive groups having C=O bonds, benzophenone, coumarin, anthraquinone, and maleimide groups can be cited. These groups can have substituents such as alkyl, alkoxy, aryl, allyloxy, cyano, alkoxycarbonyl, hydroxyl, sulfonic acid, and halogenated alkyl groups.
[0200] The solvent of the photo-alignment film-forming composition is preferably a solvent capable of dissolving the polymer having a photoreactive group and the monomer, and examples of the solvent include the solvents listed as the solvent of the above-mentioned aligning polymer composition.
[0201] The content of the polymer or monomer having a photoreactive group relative to the photoalignment film-forming composition can be appropriately adjusted according to the type of the polymer or monomer having a photoreactive group and the thickness of the photoalignment film to be manufactured, and is preferably 0.2% by mass or more, and particularly preferably in the range of 0.3 to 10% by mass. In addition, a polymer material such as polyvinyl alcohol and polyimide and a photosensitizer may be included within a range that does not significantly impair the properties of the photoalignment film.
[0202] As a method for applying the photo-alignment film-forming composition to a substrate or a protective layer, the same method as the method for applying the oriented polymer composition to a substrate or a protective layer can be cited. As a method for removing the solvent from the applied photo-alignment film-forming composition, for example, the same method as the method for removing the solvent from the oriented polymer composition can be cited.
[0203] In order to irradiate polarized light, it can be a method of directly irradiating polarized light to the product obtained by removing the solvent from the composition for forming a photo-alignment film coated on a substrate or a protective layer, or it can be a method of irradiating polarized light from the substrate or protective layer side and transmitting the polarized light. In addition, the polarized light is particularly preferably substantially parallel light. The wavelength of the irradiated polarized light is preferably a wavelength in the wavelength region where the photoreactive group of the polymer or monomer having a photoreactive group can absorb light energy. Specifically, UV (ultraviolet light) with a wavelength in the range of 250 to 400nm is particularly preferred. As a light source for irradiating the polarized light, xenon lamps, high-pressure mercury lamps, ultra-high-pressure mercury lamps, metal halide lamps, ultraviolet lasers such as KrF and ArF can be cited, and high-pressure mercury lamps, ultra-high-pressure mercury lamps and metal halide lamps are more preferred. These lamps are preferred because the luminous intensity of ultraviolet light with a wavelength of 313nm is large. Polarized light can be irradiated by irradiating the light emitted from the above-mentioned light source through an appropriate polarizer. As the polarizer, a polarizing filter, a polarizing prism such as Glan-Thompson or Glan-Taylor, or a wire grid type polarizer can be used.
[0204] It should be noted that, when rubbing or polarized light irradiation is performed, by performing masking, a plurality of regions (patterns) in which the liquid crystal alignment directions are different can be formed.
[0205] The groove alignment film is a film having a concave-convex pattern or multiple grooves (grooves) on the film surface. When liquid crystal molecules are placed on a film having multiple linear grooves arranged at equal intervals, the liquid crystal molecules will be aligned in the direction along the grooves.
[0206] As methods for obtaining a grooved orientation film, the following methods can be cited: a method of exposing the surface of a photosensitive polyimide film through an exposure mask having a slit in a pattern shape, and then developing and rinsing to form a concave-convex pattern; a method of forming a layer of a UV curable resin before curing on a plate-like original plate having grooves on the surface, and then transferring the resin layer to a substrate or a protective layer to cure it; and a method of pressing a roll-like original plate having a plurality of grooves on a film of a UV curable resin before curing formed on a substrate or a protective layer to form concave-convex, and then curing it, etc. Specifically, the methods described in Japanese Patent Publication No. 6-34976 and Japanese Patent Publication No. 2011-242743 can be cited.
[0207] In order to obtain an orientation with little orientation disorder, the width of the convex portion of the grooved orientation film is preferably 0.05 μm to 5 μm, the width of the concave portion is preferably 0.1 μm to 5 μm, and the depth of the height difference of the concave and convex is preferably 2 μm or less, more preferably 0.01 μm to 1 μm.
[0208] <Protective layer>
[0209] In the polarizing film involved in one embodiment of the present invention, the protective layer is a cured film of a composition containing a polymerizable compound (hereinafter, also referred to as a "protective layer forming composition"), which is laminated on one side or both sides of the polarizer. The so-called cured film of the protective layer forming composition refers to a film obtained by polymerizing the polymerizable compound contained in the coating film after applying the protective layer forming composition to obtain a coating film, that is, the cured film of the protective layer forming composition is a film formed by a polymer containing the polymerizable compound. The protective layer can, for example, help prevent the shrinkage and expansion of the polarizer, prevent the deterioration of the polarizing film caused by temperature, humidity, ultraviolet rays, etc., and by providing the polarizing film with a protective layer, the polarizing film involved in one embodiment of the present invention can exert stable polarizing performance. In a preferred embodiment of the present invention, from the viewpoint of obtaining a thin polarizing film, the protective layer is preferably laminated on one side of the polarizer.
[0210] In one embodiment of the present invention, the protective layer forming composition contains a monofunctional polymerizable compound (hereinafter, also referred to as "polymerizable compound (a)") as a polymerizable compound. That is, the protective layer is a cured film of a protective layer forming composition containing a polymerizable compound (a). In the present invention, the protective layer as a cured film of a protective layer forming composition is a layer obtained by applying the protective layer forming composition to a substrate or a polarizer and curing (polymerizing) the obtained coating film, and the cured film of the protective layer forming composition contains: a polymer containing a structural unit from a polymerizable compound (a). In the present invention, it is not necessary to dry the coating film obtained by applying the protective layer forming composition to a substrate or a polarizer. If the above-mentioned protective layer is a layer obtained by polymerizing the coating film obtained by applying the protective layer forming composition to a substrate or a polarizer without drying it (that is, if the content of the solvent in the protective layer forming composition is within the range described later), the obtained polarizing film can exhibit high polarization performance. When a drying step (heating step) is performed when forming the protective layer, the alignment of the dichroic compound contained in the polarizer may be disturbed. However, in the present invention, since the drying step is not required, it is considered that the alignment disturbance can be suppressed.
[0211] About the content of the polymerizable compound (a) in the protective layer forming composition, it is 60% by mass or more relative to all the polymerizable compounds contained in the protective layer forming composition, preferably 70% by mass or more, more preferably 80% by mass or more, further preferably 85% by mass or more, and particularly preferably 88% by mass or more. When the content of the polymerizable compound (a) contained in the protective layer forming composition is above the above lower limit, even if the protective layer forming composition does not contain a solvent, the fluidity of the protective layer forming composition is good, and therefore, it is not necessary to carry out a drying process, and the polarization performance of the polarizer can be suppressed to decrease with the drying process, and in addition, a polarizing film with excellent processability and thinness can be obtained. It should be noted that the upper limit of the content of the polymerizable compound (a) in the protective layer forming composition is preferably 100% by mass or less relative to all the polymerizable compounds contained in the protective layer forming composition.
[0212] The molecular weight of the polymerizable compound (a) is preferably 300 or less, more preferably 250 or less, and further preferably 210 or less. When the molecular weight of the polymerizable compound (a) contained in the protective layer forming composition is below the above upper limit, the fluidity of the protective layer forming composition is better, and therefore, the protective layer forming composition can be evenly and thinly coated on a substrate or a polarizer, and a protective layer with a more uniform thickness and a thin type can be obtained. The lower limit of the molecular weight of the polymerizable compound (a) contained in the protective layer forming composition is usually 80 or more. It should be noted that when there are multiple polymerizable compounds (a) contained in the protective layer forming composition, it is preferred that the molecular weights of all types of polymerizable compounds (a) contained in the protective layer forming composition are within the above range.
[0213] In one embodiment of the present invention, the polymerizable compound (a) includes compounds having a (meth)acryloyl group, compounds having an epoxy group, compounds having a vinyl group, and the like. In the present invention, from the viewpoint of having high polymerizability and obtaining good protective performance, the polymerizable compound (a) preferably includes a compound having a (meth)acryloyl group. It should be noted that when the polymerizable compound (a) includes a compound having a (meth)acryloyl group, the protective layer is composed of a polymer containing a structural unit derived from a compound having a (meth)acryloyl group (for example, a polymer composed of a structural unit derived from a compound having a (meth)acryloyl group).
[0214] Examples of the monofunctional (meth)acryloyl group-containing compound include (meth)acrylic acid; (meth)acrylic acid (alkyl having 1 to 16 carbon atoms) esters such as methyl (meth)acrylate, ethyl (meth)acrylate, n-butyl (meth)acrylate, sec-butyl (meth)acrylate, and tert-butyl (meth)acrylate; cyclohexyl (meth)acrylate, 2-methylcyclohexyl (meth)acrylate, tricyclo[5.2.1.0 2,6 ] (Meth)acrylate (cycloalkyl having 4 to 16 carbon atoms) esters such as decane-8-yl ester, dicyclopentanyl oxyethyl (meth)acrylate and isobornyl (meth)acrylate; (meth)acrylate (β-carboxyalkyl having 2 to 14 carbon atoms); (meth)acrylate (alkylated phenyl having 2 to 14 carbon atoms); methoxypolyethylene glycol (meth)acrylate, phenoxypolyethylene glycol (meth)acrylate; (di)alkyl (meth)acrylamide having 4 to 16 carbon atoms; β-carboxyalkyl (meth)acrylamide having 2 to 14 carbon atoms; alkylated phenyl (meth)acrylamide having 2 to 14 carbon atoms; methoxypolyethylene glycol (meth)acrylamide; phenoxypolyethylene glycol (meth)acrylamide, etc.
[0215] In a further preferred embodiment of the present invention, from the viewpoint of obtaining better protective performance, the polymerizable compound (a) preferably contains a compound having a (meth)acryloyl group and a hydroxyl group. It should be noted that when the polymerizable compound (a) contains a compound having a (meth)acryloyl group and a hydroxyl group, the protective layer is composed of a polymer containing a structural unit derived from a compound having a (meth)acryloyl group and a hydroxyl group (for example, a polymer composed of a structural unit derived from a compound having a (meth)acryloyl group and a hydroxyl group), preferably a polymer containing a structural unit derived from a compound having a (meth)acryloyl group and a structural unit derived from a compound having a (meth)acryloyl group and a hydroxyl group (for example, a polymer composed of a structural unit derived from a compound having a (meth)acryloyl group and a structural unit derived from a compound having a (meth)acryloyl group and a hydroxyl group).
[0216] In one embodiment of the present invention, the content of the compound having a (meth) acryloyl group and a hydroxyl group is preferably 5% by mass or more relative to all polymerizable compounds contained in the protective layer forming composition, more preferably 30% by mass or more, further preferably 50% by mass or more, preferably 99% by mass or less, and more preferably 95% by mass or less. When the content of the compound having a (meth) acryloyl group and a hydroxyl group in the protective layer forming composition is above the above lower limit, the dissolution inhibition effect brought by the hydroxyl group can suppress the time-dependent decrease in the polarization performance of the protective layer. When the content of the compound having a (meth) acryloyl group and a hydroxyl group in the protective layer forming composition is below the above upper limit, the hydrogen bond formation based on the hydroxyl group is reduced, and the viscosity can be reduced.
[0217] The compound having a (meth)acryloyl group and a hydroxyl group is preferably a compound represented by the following formula (1).
[0218] [Chemical formula 15]
[0219]
[0220] 〔In the formula,
[0221] n represents an integer from 1 to 12,
[0222] A 1 represents O or NH,
[0223] X 1 represents a methylene group which may have a substituent, and when n is an integer greater than 2, at least one of the methylene groups may be replaced by an oxygen atom, and the substituents may be the same or different]
[0224] When the compound having a (meth)acryloyl group and a hydroxyl group is a compound represented by the above formula (1), better protective performance can be obtained. This is presumably because when the compound exhibiting dichroism dissolves and diffuses into the protective layer, the dissolution inhibition effect brought about by the hydroxyl group at the molecular terminal of the polymer of the compound having a (meth)acryloyl group and a hydroxyl group in the protective layer can be further exerted.
[0225] In the above formula (1), n is generally an integer of 1 to 12, preferably an integer of 2 to 10, preferably an integer of 3 to 8, and preferably an integer of 4 to 6. When n is equal to or greater than the lower limit, the hydroxyl group at the molecular end is less likely to be affected by the polymer main chain, and the dissolution inhibitory effect of the hydroxyl group is more likely to be exerted. When n is equal to or less than the upper limit, X 1If n of the main chain is within the above range, when the dichroic compound dissolves and diffuses into the protective layer, the dissolution inhibition effect brought about by the hydroxyl group at the molecular terminal of the polymer of the compound having a (meth)acryloyl group and a hydroxyl group in the protective layer is more likely to be exerted.
[0226] In the above formula (1), A 1 It usually represents O or NH, preferably represents O.
[0227] In the above formula (1), X 1 represents a methylene group which may have a substituent. When n is an integer greater than 2, at least one of the methylene groups may be replaced by an oxygen atom, and the substituents may be the same or different. Examples of the substituent include aliphatic or alicyclic hydrocarbon groups having 2 to 10 carbon atoms (e.g., 2 to 5 carbon atoms) or aromatic hydrocarbon groups having 5 to 20 carbon atoms (e.g., 5 to 11 carbon atoms). X in which at least one of the methylene groups is replaced by an oxygen atom 1 , for example -(CH2CH2O) m -CH2CH2-、-(CH2CH(CH3)O) m -CH2CH(CH3)- [wherein m is an integer of 1 to 3], etc.
[0228] In one embodiment of the present invention, the content of the compound represented by the above formula (1) is preferably 40% by mass or more, more preferably 50% by mass or more, more preferably 65% by mass or more, preferably 99% by mass or less, and more preferably 95% by mass or less, relative to all polymerizable compounds contained in the protective layer forming composition. When the content of the compound represented by the above formula (1) in the protective layer forming composition is above the above lower limit, due to the dissolution inhibition effect brought by the hydroxyl group, the time-dependent decrease in the polarization performance of the protective layer can be suppressed. In addition, since the fluidity of the protective layer forming composition is particularly good, the polarization performance of the polarizer can be further suppressed from decreasing with the drying process. When the content of the compound represented by the above formula (1) in the protective layer forming composition is below the above upper limit, the hydrogen bond formation based on the hydroxyl group is reduced, which can reduce the viscosity.
[0229] Examples of the compound having a (meth)acryloyl group and a hydroxyl group include (meth)acrylic acid (hydroxyalkyl having 4 to 16 carbon atoms), (meth)acrylic acid (hydroxycycloalkyl having 4 to 16 carbon atoms), (meth)acrylic acid (hydroxyalkylated phenyl having 2 to 14 carbon atoms), polyethylene glycol (meth)acrylate, and hydroxy(di)alkyl (meth)acrylamide having 4 to 16 carbon atoms, hydroxyalkylated phenyl (meth)acrylamide having 2 to 14 carbon atoms, polyethylene glycol (meth)acrylamide, etc. More preferred are (meth)acrylic acid (hydroxyalkyl having 4 to 6 carbon atoms) and (meth)acrylic acid (hydroxycycloalkyl having 4 to 16 carbon atoms), and even more preferred are acrylate (hydroxyalkyl having 4 to 6 carbon atoms) and acrylate (hydroxycycloalkyl having 4 to 16 carbon atoms).
[0230] In a preferred embodiment of the present invention, the composition for forming a protective layer may contain, as a polymerizable compound, in addition to the polymerizable compound (a), a polymerizable compound having two or more functional groups (hereinafter also referred to as "polymerizable compound (b)"). That is, the cured film of the composition for forming a protective layer as a protective layer may contain a polymer composed of structural units derived from the polymerizable compound (a) and structural units derived from the polymerizable compound (b).
[0231] In one embodiment of the present invention, as the polymerizable compound (b), similarly to the polymerizable compound (a), there can be mentioned compounds having a (meth)acryloyl group, compounds having an epoxy group, compounds having a vinyl group, etc. In the present invention, the polymerizable compound (b) is preferably a compound having a (meth)acryloyl group from the viewpoint of having high polymerizability and obtaining good protective performance.
[0232] Examples of the bifunctional polymerizable compound include 1,3-butanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, polyethylene glycol diacrylate, bis(acryloyloxyethyl) ether of bisphenol A, ethoxylated bisphenol A di(meth)acrylate, propoxylated neopentyl glycol di(meth)acrylate, ethoxylated neopentyl glycol di(meth)acrylate, 3-methylpentanediol di(meth)acrylate, and methylenebisacrylamide.
[0233] Examples of trifunctional or higher-functional polymerizable compounds include:
[0234] Trimethylolpropane tri(meth)acrylate; Pentaerythritol tri(meth)acrylate; Tri(2-hydroxyethyl)isocyanurate tri(meth)acrylate; Ethoxylated trimethylolpropane tri(meth)acrylate; Propoxylated trimethylolpropane tri(meth)acrylate; Pentaerythritol tetra(meth)acrylate; Dipentaerythritol penta(meth)acrylate; Dipentaerythritol hexa(meth)acrylate; Tripentaerythritol tetra(meth)acrylate; Tripentaerythritol penta(meth)acrylate; Tripentaerythritol hexa(meth)acrylate; Tripentaerythritol hepta(meth)acrylate; Tripentaerythritol octa(meth)acrylate;
[0235] The reaction product of pentaerythritol tri(meth)acrylate and acid anhydride; The reaction product of dipentaerythritol penta(meth)acrylate and acid anhydride;
[0236] The reaction product of tripentaerythritol hepta(meth)acrylate and anhydride;
[0237] Caprolactone modified trimethylolpropane tri(meth)acrylate; Caprolactone modified pentaerythritol tri(meth)acrylate; Caprolactone modified tri(2-hydroxyethyl)isocyanurate tri(meth)acrylate; Caprolactone modified pentaerythritol tetra(meth)acrylate; Caprolactone modified dipentaerythritol penta(meth)acrylate; Caprolactone modified dipentaerythritol hexa(meth)acrylate; Caprolactone modified tripentaerythritol tetra(meth)acrylate; Caprolactone modified tripentaerythritol Pentaerythritol penta (meth) acrylate; caprolactone-modified tripentaerythritol hexa (meth) acrylate; caprolactone-modified tripentaerythritol hepta (meth) acrylate; caprolactone-modified tripentaerythritol octa (meth) acrylate; the reaction product of caprolactone-modified pentaerythritol tri (meth) acrylate and anhydride; the reaction product of caprolactone-modified dipentaerythritol penta (meth) acrylate and anhydride, and the reaction product of caprolactone-modified tripentaerythritol hepta (meth) acrylate and anhydride. It should be noted that in the specific examples of multifunctional acrylates recorded here, the so-called (meth) acrylate refers to acrylate or methacrylate. In addition, the so-called caprolactone modification refers to the introduction of a ring-opened body or a ring-opened polymer of caprolactone between the alcohol-derived portion of the (meth) acrylate compound and the (meth) acryloyloxy group.
[0238] In the present invention, from the viewpoint of obtaining a protective layer with high surface hardness, the protective layer-forming composition preferably contains a polymerizable compound (b) having two or more functions, especially three or more functions, and the protective layer-forming composition more preferably contains a polymerizable compound (b) having six functions. It should be noted that the protective layer-forming composition may contain one or more polymerizable compounds (b). When the protective layer-forming composition contains a polymerizable compound (b), the polymer of the polymerizable compound contained in the protective layer is cross-linked, which not only improves the surface hardness of the protective layer, but also reduces the dependence on the external environment in which the polarizing film is located.
[0239] When the protective layer forming composition includes a polymerizable compound (b), relative to all polymerizable compounds contained in the protective layer forming composition, the content of the polymerizable compound (b) contained in the protective layer forming composition is preferably 20% by mass or less, more preferably 15% by mass or less, more preferably 12% by mass or less, preferably 1% by mass or more, more preferably 5% by mass or more, and more preferably 8% by mass or more. When the content of the polymerizable compound (b) contained in the protective layer forming composition is below the above-mentioned upper limit, even if the protective layer forming composition does not include a solvent, the fluidity of the protective layer forming composition is also good, therefore, there is no need to carry out a drying process, the polarization performance of the polarizer can be suppressed to decrease with the drying process, and in addition, a thin polarizing film can be obtained. When the content of the polymerizable compound (b) contained in the protective layer forming composition is above the above-mentioned lower limit, a protective layer with a high surface hardness can be obtained.
[0240] It should be noted that the composition used to prepare the protective layer contains a large amount of difunctional or higher, especially trifunctional or higher (especially hexafunctional or higher) polymerizable compounds. As a result, the surface hardness of the obtained protective layer can be improved by suppressing the transfer of the compound showing dichroism. On the other hand, since difunctional or higher, especially trifunctional or higher (especially hexafunctional or higher) polymerizable compounds have a bulky structure, in order to obtain a uniform and thin protective layer, it is necessary to increase the content of the solvent in the protective layer to improve the fluidity. However, the added solvent can induce the transfer of the compound showing dichroism. In a preferred embodiment of the present invention, by using the above-mentioned specific protective layer-forming composition, the transfer of the compound showing dichroism can be suppressed, and a uniform and thin protective layer can be obtained.
[0241] In the present invention, the content of the structural unit derived from the polymerizable compound (a) in the protective layer is preferably 60% by mass or more, more preferably 70% by mass or more, further preferably 80% by mass or more, particularly preferably 85% by mass or more, especially preferably 88% by mass or more, and preferably 100% by mass or less, relative to the polymer constituting the protective layer. When the content of the structural unit derived from the polymerizable compound (a) in the protective layer is above the above lower limit, the fluidity of the protective layer forming composition is good, and therefore, no drying process is required, and the polarization performance of the polarizer can be suppressed from decreasing along with the drying process. In addition, a polarizing film with excellent processability and a thin type can be obtained.
[0242] The protective layer-forming composition may contain a polymer or oligomer obtained by polymerizing a polyfunctional acrylate. Examples of the polymer or oligomer obtained by polymerizing a polyfunctional acrylate include aliphatic, alicyclic, or aromatic urethane acrylate polymers or oligomers.
[0243] The content of the polymer or oligomer obtained by polymerizing the multifunctional acrylate in the protective layer forming composition is preferably 20% by mass or less, more preferably 15% by mass or less, more preferably 10% by mass or less, preferably 1% by mass or more, more preferably 5% by mass or more, and more preferably 8% by mass or more, relative to the solid content of the protective layer forming composition. When the content of the above-mentioned polymer or oligomer is below the above-mentioned upper limit, the fluidity of the protective layer forming composition is good, and a uniform and thin protective layer can be obtained. When the content of the above-mentioned polymer or oligomer is above the above-mentioned lower limit, the time-dependent decrease in the polarization performance of the obtained polarizing film can be further suppressed. It should be noted that the so-called solid content refers to all the components obtained by removing the solvent from the protective layer forming composition.
[0244] The protective layer forming composition may include a solvent. Regarding the content of the solvent in the protective layer forming composition, relative to the total amount of the protective layer forming composition, it is preferably 5% by mass or less, more preferably 3% by mass or less, further preferably 1% by mass or less, and particularly preferably 0% by mass. When the content of the solvent in the protective layer forming composition is below the above-mentioned upper limit, even if the drying process is not performed when the polarizing film to which one embodiment of the present invention relates is made, the content of the solvent in the protective layer can be suppressed to a low level, and therefore, the polarizing performance of the polarizing film caused by the drying process will not decrease, and the polarizing performance of the polarizing film can be suppressed over time. It should be noted that the content of the solvent in the protective layer forming composition is particularly preferably 0% by mass (preferably 5% by mass or less). In the present invention, since the fluidity of the protective layer forming composition is good, even if the protective layer forming composition does not contain a solvent (or the content of the solvent in the protective layer forming composition is very small), a uniform and thin coating film can be obtained. Relative to the total amount of the protective layer forming composition, the lower limit of the content of the solvent in the protective layer forming composition is usually 0% by mass or more.
[0245] According to the present invention, a protective layer can be prepared without performing a drying process, and the solvent content in the protective layer forming composition can be extremely reduced as described above. Therefore, the decrease in the polarization performance of the polarizing film during the polarizing film manufacturing process can be suppressed, and the decrease in the polarization performance of the polarizing film over time can also be suppressed.
[0246] In addition, as required, the protective layer forming composition may contain additives commonly used in curable compositions. Such additives include, for example, the above-mentioned polymerization initiators, sensitizers, polymerization inhibitors, leveling agents and reactive additives, as well as ion traps, antioxidants, chain transfer agents, polymerization accelerators (polyols, etc.), sensitizers, light stabilizers, tackifiers, thermoplastic resins, fillers, flow regulators, plasticizers, defoamers, silane coupling agents, pigments, antistatic agents, and ultraviolet absorbers.
[0247] The content of the polymerization initiator in the protective layer-forming composition can be appropriately adjusted according to the type and amount of the polymerizable compound, and from the viewpoint of initiator efficiency, it is generally 0.1 to 40 parts by mass, preferably 0.2 to 30 parts by mass, more preferably 0.5 to 10 parts by mass, and further preferably 0.5 to 8 parts by mass, relative to 100 parts by mass of the polymerizable compound.
[0248] When the protective layer forming composition contains a leveling agent, from the viewpoint of making the obtained protective layer smooth, the content of the leveling agent in the protective layer forming composition is preferably 0 to 6 parts by mass, more preferably 0.01 to 5 parts by mass, further preferably 0.05 to 5 parts by mass, and particularly preferably 0.08 to 3 parts by mass relative to 100 parts by mass of the polymerizable compound. Two or more types of leveling agents may be contained.
[0249] The viscosity of the protective layer forming composition is preferably 120cps or less at 27°C, more preferably 80cps or less, and further preferably 50cps or less. When the viscosity of the protective layer forming composition at 27°C is below the above upper limit, the fluidity of the protective layer forming composition is better, so the protective layer forming composition can be evenly and thinly applied to the substrate or polarizer, and a protective layer with a more uniform thickness and a thin type can be obtained, and in the manufacturing process of the polarizing film, the pump efficiency is excellent. It should be noted that the lower limit of the viscosity of the protective layer forming composition is usually 5cps or more. The viscosity can be measured according to JIS K7367.
[0250] In a preferred embodiment, when the content of the solvent in the protective layer forming composition is within the above range, the viscosity of the protective layer forming composition is equal to or less than the above upper limit.
[0251] The solid content of the protective layer forming composition is preferably 95% by mass or more, and more preferably 100% by mass, relative to the total mass of the protective layer forming composition. When the solid content of the composition is above the lower limit, the protective layer forming composition can be uniformly and thinly applied to a substrate or a polarizer without a drying step, and a protective layer with a more uniform thickness and a thin type can be obtained, thereby obtaining a polarizing film with excellent polarization performance and heat resistance.
[0252] The thickness of the protective layer is not particularly limited, but is usually 10 μm or less, preferably 0.15 to 5 μm, more preferably 0.5 to 4 μm, and further preferably 1.0 to 3 μm.
[0253] The surface of the protective layer not bonded to the polarizer may have a surface treatment layer, for example, an optical layer such as a hard coat layer, an antireflection layer, an anti-sticking layer, an anti-glare layer or a diffusion layer.
[0254] The hard coating layer is a layer for the purpose of preventing the surface of the polarizing film from being damaged, and can be formed, for example, by attaching a cured film having excellent hardness and sliding properties obtained from an ultraviolet curing resin such as an acrylic or silicone resin to the surface of the protective layer. The anti-reflection layer is a layer for the purpose of preventing external light from being reflected on the surface of the polarizing film, and can be achieved by forming an anti-reflection film according to a conventional method. In addition, the anti-adhesion layer is a layer for the purpose of preventing adhesion with adjacent layers.
[0255] In addition, the anti-glare layer is a layer for the purpose of preventing the visibility of the polarizing film's transmitted light from being hindered by the reflection of external light on the surface of the polarizing film. For example, the anti-glare layer can be formed by giving a fine concave-convex structure to the surface of the protective layer by using a roughening method based on a sandblast method, an embossing method, a method of matching transparent particles, etc. As particles contained in order to form the above-mentioned surface fine concave-convex structure, for example, inorganic particles with conductivity formed by silicon dioxide, aluminum oxide, titanium oxide, zirconium oxide, tin oxide, indium oxide, cadmium oxide, antimony oxide, etc., transparent particles such as organic particles formed by crosslinked or uncrosslinked polymers, etc., with an average particle size of 0.5 to 50 μm, can be cited. In the case of forming a fine concave-convex structure on the surface, the content of the particles is usually 2 to 50 parts by mass, preferably 5 to 25 parts by mass, relative to 100 parts by mass of the transparent resin forming the surface fine concave-convex structure. The anti-glare layer may also function as a diffusion layer for diffusing light transmitted through the polarizing film to expand the viewing angle (viewing angle expansion function, etc.).
[0256] It should be noted that the antireflection layer, anti-sticking layer, diffusion layer, anti-glare layer, etc. mentioned above can be provided on the protective layer itself for integration, or can be provided as an optical layer in the form of a layer independent of the protective layer.
[0257] In one embodiment of the present invention, the polarizing film has excellent heat resistance. The so-called heat resistance here means that the polarizing performance of the polarizing film is not easy to change over time under high temperature conditions. For example, the change rate of the visibility-corrected polarization degree Py (polarization change rate) after being kept in a dry atmosphere at 150°C for 1 hour is preferably 10% or less, more preferably 5% or less, and further preferably 3% or less, and the change rate of the visibility-corrected monomer transmittance Ty after being kept for 1 hour under the same conditions (monomeric transmittance change rate) is preferably 10% or less, more preferably 5% or less, and further preferably 3% or less, based on the visibility-corrected monomer transmittance Ty before being kept. In the method of making a display device using a polarizing film, a process of heating the polarizing film is sometimes performed. Sometimes, the polarization performance of the polarizing film is degraded due to this process, but the polarizing film involved in one embodiment of the present invention has excellent heat resistance, so it is not easy to degrade the polarization performance during the process of manufacturing the display device, and a display device with excellent image display function can be obtained. It should be noted that the lower limits of the polarization degree change rate and the single transmittance change rate are usually above 0%.
[0258] The visibility-corrected transmittance (Ty) and the visibility-corrected polarization degree (Py) in this specification can be measured as follows.
[0259] The transmittance (T) in the transmission axis direction was measured in the wavelength range of 380 nm to 780 nm by a double beam method using a spectrophotometer (UV-3150 manufactured by Shimadzu Corporation) with a folder equipped with a polarizing element. 1 ) and the transmittance along the absorption axis (T 2 ). For the folder, a mesh that blocks 50% of the light is set on the reference side. The transmittance at each wavelength is calculated using the following formula (2), and then the visibility correction is performed using the 2-degree field of view (C light source) of JIS Z 8701 to calculate the visibility-corrected transmittance (Ty). The polarization degree at each wavelength is calculated using the following formula (3), and then the visibility correction is performed using the 2-degree field of view (C light source) of JIS Z 8701 to calculate the visibility-corrected polarization degree (Py).
[0260] Single body transmittance (%) = (T 1 +T 2 ) / twenty two)
[0261] Polarization degree (%) = {(T 1 -T 2 ) / (T 1 +T 2 )}×100 (3)
[0262] The polarizing film can be manufactured, for example, by a method comprising the following steps:
[0263] A coating step of coating the protective layer-forming composition containing a polymerizable compound on the polarizer containing the compound exhibiting dichroism to form a coating film; and
[0264] A polymerization step of polymerizing the polymerizable compound to form a protective layer.
[0265] In addition, the coating film is cured by polymerizing the polymerizable compound.
[0266] In the polymerization step, the polymerizable compound may be polymerized by heating or irradiating with active energy rays. In a preferred embodiment of the present invention, the polymerizable compound is polymerized by irradiating with active energy rays from the viewpoint of improving the polarization performance and heat resistance of the obtained polarizing film. Examples of active energy rays include ultraviolet rays and electron beams.
[0267] In the present invention, there is no need to perform a drying process for drying the polarizing film. If a drying process (heating process) is performed when preparing the protective layer, there is a situation where the orientation of the compound showing dichroism contained in the polarizer is disturbed, but according to the present invention, since a drying process is not required, the disorder of the orientation can be suppressed. As a result, a thin polarizing film having a protective layer with a low solvent content can be manufactured, and the obtained polarizing film has excellent polarization performance and heat resistance. It should be noted that heating can also be performed, but for example, it is preferably heated at a temperature below 40°C.
[0268] In addition, the polarizing film may also be manufactured by other methods, for example, by a method including the following steps:
[0269] A coating step of coating the protective layer-forming composition containing a polymerizable compound on a substrate to form a coating film;
[0270] A polymerization step of polymerizing the polymerizable compound to form a protective layer; and
[0271] A polarizer forming step is to form a polarizer on the protective layer.
[0272] A polarizer may also be formed after an orientation film is formed on the protective layer. It should be noted that the substrate may also be removed after the protective layer is formed. In addition, a coating step (coating the protective layer-forming composition containing a polymerizable compound on the polarizer to form a coating film) and a polymerization step (polymerizing the polymerizable compound to form a protective layer) may also be performed after the polarizer formation step to manufacture a polarizing film in which protective layers are arranged on both sides of the polarizer. An adherend such as a display device body may also be used instead of a substrate.
[0273] In the present invention, as the substrate, a glass substrate and a plastic substrate can be cited, and a plastic substrate is preferred. In view of the fact that roll-to-roll processing can be performed and productivity is high, a plastic substrate is more preferred than a glass substrate. As the plastic constituting the plastic substrate, for example, polyolefins such as polyethylene, polypropylene, and norbornene polymers; cyclic olefin resins; polyvinyl alcohol; polyethylene terephthalate; polymethacrylate; polyacrylate; cellulose esters such as triacetyl cellulose, diacetyl cellulose, and cellulose acetate propionate; polyethylene naphthalate; polycarbonate; polysulfone; polyether sulfone; polyether ketone; plastics such as polyphenylene sulfide and polyphenylene ether can be cited.
[0274] Examples of commercially available cellulose ester substrates include “Fuji TAC Film” (manufactured by Fuji Photo Film Co., Ltd.); “KC8UX2M”, “KC8UY”, and “KC4UY” (all manufactured by Konica Minolta Opto Co., Ltd.).
[0275] Examples of commercially available cyclic olefin resins include "Topas" (registered trademark) (manufactured by Ticona (Germany)), "ARTON" (registered trademark) (manufactured by JSR Corporation), "ZEONOR" (registered trademark), "ZEONEX" (registered trademark) (manufactured by ZEON Corporation of Japan) and "APEL" (registered trademark) (manufactured by Mitsui Chemicals, Inc.). Such cyclic olefin resins can be made into films as substrates using known means such as solvent casting and melt extrusion. Commercially available cyclic olefin resin substrates can also be used. Examples of commercially available cyclic olefin resin substrates include "ESCENA" (registered trademark), "SCA40" (registered trademark) (manufactured by Sekisui Chemical Co., Ltd.), "ZEONORFILM" (registered trademark) (manufactured by OPTES Corporation) and "ARTONFILM" (registered trademark) (manufactured by JSR Corporation).
[0276] In other embodiments of the present invention, an elliptically polarizing plate and a circularly polarizing plate having the above-mentioned polarizing film and a phase difference film can be provided. In one embodiment of the present invention, when a phase difference film is stacked on the above-mentioned polarizing film, it is preferably stacked in a manner that the slow axis (optical axis) of the phase difference film and the absorption axis of the polarizing film are substantially 45°. By stacking in a manner that the slow axis (optical axis) of the phase difference film and the absorption axis of the polarizing film are substantially 45°, a function as a circular polarizing plate can be obtained. In addition, it is also possible to stack in a manner that the slow axis of the phase difference film and the absorption axis of the polarizing film are substantially consistent or orthogonal. By making the slow axis of the phase difference film and the absorption axis of the polarizing film substantially consistent or orthogonal, it can also function as an optical compensation film. It should be noted that the so-called substantially 45° is generally in the range of 45±5°; the so-called substantially consistent or orthogonal is generally in the range of 0±5° or 90±5°.
[0277] The elliptically polarizing plate and the circularly polarizing plate can be produced, for example, by a method including applying an adhesive to one surface of a polarizing film and bonding the polarizing film to a retardation film via the adhesive.
[0278] It should be noted that the so-called phase difference film refers to an optical film showing optical anisotropy, which is a film used to convert linear polarized light into circular polarized light, elliptically polarized light, or conversely, to convert circular polarized light or elliptically polarized light into linear polarized light. As a phase difference film, for example, a polymer film formed by stretching a polymer such as polyvinyl alcohol, polycarbonate, polyester, polyarylate, polymethacrylate, polyimide, polyolefin, polycycloolefin (norbornene, tetracyclododecene or polymers of their derivatives), polystyrene, polysulfone, polyethersulfone, polyvinylidene fluoride / polymethyl methacrylate, liquid crystal polyester, acetyl cellulose, ethylene-vinyl acetate copolymer saponification, polyvinyl chloride, etc. to about 1.01 to 6 times to obtain a stretched film, etc. Among them, it is preferred to uniaxially stretch or biaxially stretch a polycarbonate film or a polycycloolefin film to obtain a polymer film. In addition, a film showing optical anisotropy by coating and orientation of a liquid crystal compound can also be used as a phase difference film.
[0279] The above-mentioned retardation film preferably satisfies the following formula (X):
[0280] Re(450nm) / Re(550nm)<1 (X)
[0281] In the above case, the retardation film has reverse wavelength dispersion, and therefore, coloration of a display device having the retardation film when displaying black can be reduced.
[0282] The value of Re(450nm) / Re(550nm) can be appropriately selected. Note that Re(λ) represents the front phase difference value with respect to light having a wavelength of λnm.
[0283] In other embodiments of the present invention, a display device having the above-mentioned polarizing film, elliptically polarizing plate or circularly polarizing plate may also be provided. The so-called display device refers to a device having a display element, and as a light source, it includes a light-emitting element or a light-emitting device. Examples of the display device include a liquid crystal display device, an electroluminescent (EL) display device, an inorganic electroluminescent (EL) display device, a touch panel display device, an electron emission display device (such as a field emission display device (FED), a surface field emission display device (SED)), an electronic paper (a display device using electronic ink, an electrophoretic element, a plasma display device, a projection display device (such as a grating light valve (GLV)) display device, a display device having a digital micromirror device (digitalmicromirror device)(DMD) display device) and piezoelectric ceramic display, etc. The liquid crystal display device includes any one of a transmissive liquid crystal display device, a semi-transmissive liquid crystal display device, a reflective liquid crystal display device, a direct-view liquid crystal display device and a projection liquid crystal display device. These display devices can be display devices that display two-dimensional images, or they can be stereoscopic display devices that display three-dimensional images. In particular, the above-mentioned polarizing film, elliptically polarizing plate and circularly polarizing plate can be effectively used in liquid crystal display devices and electroluminescent (EL) display devices. Other embodiments of the present invention involve a display device having a polarizing film with excellent polarization performance and heat resistance, and therefore, the image display function is excellent and can stably perform this function over time.
[0284] [Example]
[0285] The present invention will be further described in detail below by way of examples, but the present invention is not limited to these examples. It should be noted that "%" and "parts" in the examples and comparative examples represent "mass %" and "mass parts" respectively unless otherwise specified.
[0286] [Manufacturing of polarizer-forming composition]
[0287] The following components were mixed and stirred at 80° C. for 1 hour to obtain a polarizer-forming composition. As a compound exhibiting dichroism, an azo dye described in Examples of JP-A-2015-165302 was used.
[0288] (Non-coloring polymerizable liquid crystal compound)
[0289] [Chemical formula 16]
[0290]
[0291] [Chemical formula 17]
[0292]
[0293] (Compounds showing dichroism)
[0294] [Chemical formula 18]
[0295]
[0296] [Chemical formula 19]
[0297]
[0298] [Chemical formula 20]
[0299]
[0300] (Other ingredients)
[0301] Polymerization initiator: 2-dimethylamino-2-benzyl-1-(4-morpholinophenyl)butan-1-one (IRGACURE369; manufactured by Ciba Specialty Chemicals) 6 parts
[0302] Leveling agent: 0.5 parts of polyacrylate compound (BYK-361N; manufactured by BYK-Chemie)
[0303] Solvent: 350 parts of o-xylene
[0304] 〔Measurement of phase transition temperature〕
[0305] A 2 mass % aqueous solution of polyvinyl alcohol (polyvinyl alcohol 1000 completely saponified type, manufactured by Wako Pure Chemical Industries, Ltd.) (oriented polymer composition) was applied to a glass substrate by spin coating and dried to form a film with a thickness of 100 nm. Next, the surface of the obtained film was subjected to a rubbing treatment to form an oriented film. The rubbing treatment was performed using a semi-automatic rubbing device (trade name: LQ-008, manufactured by Choyo Kogaku Co., Ltd.) and a cloth (trade name: YA-20-RW, manufactured by Yoshikawa Chemical Industry Co., Ltd.) at a pressure of 0.15 mm, a rotation speed of 500 rpm, and a speed of 16.7 mm / s.
[0306] The polarizer-forming composition was applied to the oriented film prepared in the above manner by spin coating, heated and dried on a heating plate at 120°C for 1 minute, and then rapidly cooled to room temperature to form a dry film on the oriented film. After the dry film was heated to 120°C on the heating plate again, it was observed with a polarizing microscope while cooling, thereby measuring the phase transition temperature. As a result, it was confirmed that the phase transition was to the nematic liquid crystal phase at 115°C, the phase transition was to the smectic A phase at 105°C, and the phase transition was to the smectic B phase at 74°C.
[0307] [Manufacturing of protective layer-forming composition (coating solutions (1) to (14))]
[0308] As shown in Table 1, the components were mixed at the mass ratios described and stirred at room temperature for 1 hour to obtain coating liquids (1) to (14) as protective layer-forming compositions. The viscosities of the obtained coating liquids (1) to (14) were measured in accordance with JIS K7367. The results are shown in Table 1.
[0309] [Table 1]
[0310]
[0311] In Table 1,
[0312] A1 is isobornyl acrylate,
[0313] A2 is 4-hydroxybutyl acrylate,
[0314] A3 is 1,4-cyclohexanedimethanol monoacrylate,
[0315] A4 is dimethyl acrylamide,
[0316] A5 is dipentaerythritol hexaacrylate,
[0317] B1 is UV-5650B manufactured by Nippon Synthetic Chemical Industry Co., Ltd.
[0318] B2 is UV-3000B manufactured by Nippon Synthetic Chemical Industry Co., Ltd.
[0319] C1 is 3,4-epoxycyclohexylmethyl 3,4-epoxycyclohexanecarboxylate,
[0320] C2 is 2-ethylhexyl glycidyl ether,
[0321] D1 is IRGACURE907 manufactured by BASF,
[0322] D2 is CPI-100P made by San-Apro,
[0323] E1 is MEGAFACE F-554 manufactured by DIC Corporation.
[0324] [Example 1] Production and evaluation of polarizer
[0325] 1. Formation of polarizer
[0326] The polarizer-forming composition is applied to the alignment film obtained above by spin coating, and is dried by heating on a hot plate at 120° C. for 1 minute, and then rapidly cooled to below room temperature (a temperature at which a smectic liquid crystal phase is exhibited when the temperature is lowered), thereby forming a first dried film on the alignment film. The liquid crystal state of the non-coloring polymerizable liquid crystal compound contained in the first dried film is a smectic B phase.
[0327] Next, a UV irradiation device (SPOT CURE SP-7; manufactured by USHIO INC.) was used to irradiate the sample at 2400 mJ / cm 2 The first dried film was irradiated with ultraviolet light at an exposure amount of 100 nm (based on 365 nm), thereby polymerizing the non-coloring polymerizable liquid crystal compound contained in the first dried film while maintaining the liquid crystal state of the non-coloring polymerizable liquid crystal compound, and a polarizer was formed from the first dried film to obtain a laminate 1. The thickness of the polarizer at this time was measured using a laser microscope (OLS3000 manufactured by Olympus Corporation) and the result was 1.8 μm.
[0328] 2. X-ray diffraction measurement
[0329] The polarizer of the obtained laminate 1 was measured by X-ray diffraction using an X'Pert PRO MPD (manufactured by Spectris Corporation). X-rays were incident from the rubbing direction through a fixed divergence slit of 1 / 2° (the X-rays were generated using Cu as a target under the conditions of an X-ray tube current of 40 mA and an X-ray tube voltage of 45 kV). The measurement was performed by scanning in the scanning range of 2θ=4.0~40.0° with a step size of 2θ=0.01671°. As a result, a sharp diffraction peak (Bragg peak) with a half-width (FWHM) of about 0.187° was obtained near 2θ=20.22°. In addition, even if the X-rays were incident from a direction perpendicular to the rubbing direction, the same result was obtained. The ordered period (d) obtained from the peak position is about It can be seen that a structure reflecting a high-order smectic liquid crystal phase is formed.
[0330] 3. Manufacturing of polarizing film by forming a protective layer
[0331] The protective layer-forming composition of the coating liquid (1) was applied onto the polarizer of the laminate 1 by spin coating, and a UV irradiation device (SPOT CURE SP-7; manufactured by USHIO INC.) was used to irradiate the polarizer at 400 mJ / cm 2The polarizing film (1) was manufactured by irradiating the polarizer with ultraviolet light at an exposure amount (based on 365 nm) of 1.5 to 2.5 nm to form a protective layer on the polarizer. The protective layer at this time was measured with a laser microscope (OLS3000 manufactured by Olympus Corporation) and found to be 2.8 μm.
[0332] 4. Heat resistance test of polarizing film
[0333] The visibility-corrected polarization degree Py and the visibility-corrected single transmittance Ty of the obtained polarizing film (1) were measured using a spectrophotometer (UV-3150 manufactured by Shimadzu Corporation). Next, the polarizing film (1) was placed in a drying oven at 150° C. After 1 hour, the visibility-corrected polarization degree Py and the visibility-corrected single transmittance Ty were measured again, and the change rate before and after the heat resistance test was calculated. The results are shown in Table 2.
[0334] [Examples 2 to 12]
[0335] Polarizing films (2) to (12) were produced in the same manner as in Example 1 except that coating solutions (2) to (12) were used instead of coating solution (1). The polarizing films (2) to (12) were subjected to a durability test. The results are shown in Table 2. The protective layers of the polarizing films (2) to (12) were 2.8 μm thick.
[0336] [Comparative Examples 1 and 2]
[0337] Polarizing films (13) and (14) were prepared in the same manner as in Example 1 except that coating solution (1) or coating solution (14) was used instead of coating solution (1). The polarizing films (13) and (14) were subjected to a durability test. The results are shown in Table 2. It should be noted that the protective layer of each of the polarizing films (13) and (14) was 2.8 μm.
[0338] The content of the monofunctional polymerizable compound (polymerizable compound (a) content), the content of the compound having a methacryloyl group and a hydroxyl group (hydroxyl group-containing compound content), and the content of the compound represented by formula (1) (compound (1) content) in the coating liquids (1) to (14) were calculated based on the total polymerizable compounds. The results are shown in Table 2.
[0339] [Table 2]
[0340]
[0341] In Examples 1 to 12, the change rates of the polarization degree Py and the single transmittance Ty were small, and the temporal change of the polarization performance was suppressed. On the other hand, the results of Comparative Examples 1 and 2 showed that the change rates of the polarization degree Py and the single transmittance Ty were large.
Claims
1. A polarizing film, comprising a protective layer and a polarizer containing a dichroic compound, wherein the protective layer is a cured film of a composition containing a polymerizable compound, and the content of the monofunctional polymerizable compound in the composition is 70% by mass or more relative to the total polymerizable compounds contained in the composition, The monofunctional polymerizable compound includes a compound represented by the following formula (1) having a (meth)acryloyl group and a hydroxyl group, [Chemical formula 1] In formula (1), n represents an integer of 1 to 12, A 1 represents O or NH, X 1 represents a methylene group which may have a substituent, when n is an integer greater than or equal to 2, at least one of the methylene groups may be replaced by an oxygen atom, the substituents may be the same or different, and the viscosity of the composition is greater than or equal to 12 cps and less than or equal to 26 cps at 27° C., The thickness of the protective layer is less than 10 μm.
2. The polarizing film according to claim 1, wherein The polarizer further includes a polymer of a non-coloring polymerizable liquid crystal compound.
3. The polarizing film according to claim 2, wherein: The polarizer contains a polymer of a non-coloring polymerizable liquid crystal compound in an amount of 80% by mass or more relative to the total mass of the polarizer, The polymer of the non-coloring polymerizable liquid crystal compound exhibits a smectic liquid crystal phase, The compound exhibiting dichroism is contained in a polymer-aligned form with the non-coloring polymerizable liquid crystal compound.
4. The polarizing film according to any one of claims 1 to 3, wherein The compound showing dichroism is an azo dye. 5 . A circularly polarizing plate comprising the polarizing film according to claim 1 and a retardation film.
6. The circularly polarizing plate according to claim 5, wherein: The phase difference film satisfies the following formula (X): Re(450nm) / Re(550nm)<1(X) In the formula (X), Re(λ) represents the front phase difference value with respect to light of wavelength λ nm. 7 . A display device comprising the polarizing film according to claim 1 , or the circularly polarizing plate according to claim 5 or 6 .
Citation Information
Patent Citations
JP1972019156U
Liquid crystal display element
JP1994034976A
Dichroic Guest-Host Polarizers Containing Oriented Polymer Films
JP2007510946A
Alignment layer and manufacturing method thereof, phase difference element and manufacturing method thereof, and display device
JP2011242743A
Polarizer and method for manufacturing the same
JP2013037353A